The Role Moderating of Industrial Competition in The Effect Of Corporate Governance and Risk Management on Sustainability Performance - Rakhmawati Oktavianna; Holiawati Holiawati; Endang Ruhiyat (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This research aims to examine and analyze the role of industrial competition in moderating the relationship between corporate governance and risk management and sustainability. This type of research is associative quantitative. The population is industrial companies listed on the Indonesia Stock Exchange in 2017-2021, with sample 33 industrial companies. Determination of number of samples uses purposive sampling method. The hypothesis was tested using eviews 10 program with panel data regression and Moderated Regression Analysis (MRA). The research results show that governance has no effect on sustainability performance, but risk management has an effect on sustainability performance. Meanwhile, Industrial Competition strengthens the relationship between governance and sustainability performance and Industrial Competition weakens the relationship between risk management and sustainability performance